The Effect of Compensation, Motivation and Work Environment on Performance of BDE Yogyakarta Bank Employees - Hapsari, Retno; Widarta (ASIAN PUBLISHER, 2023)
This research aims to test the influence of the Variable Influence of Compensation, Motivation and Work Environment partially and simultaneously on the variable Performance of Bank BDE Yogyakarta employees. The population in this research is Bank BDE Yogyakarta employees. Sampling was done by using the purposive sampling technique and obtained a sample of 123 respondents. Data collection in this research uses the questionnaire method. The data analysis method used is multiple linear regression analysis. The results of the research show that the variables Compensation, Motivation and Work Environment partially have a positive and significant effect on the variable Employee Performance. The results of the F test show that the level of significance is 0.000 smaller than the level of significance α = 0.05 so that the variables Compensation, Motivation and Work Environment simultaneously have a significant effect on employee performance.